Optimization and Establishment of Bullying Prevention and Case Management System for Adolescent in Junior High Schools - Gunawan, Ashfan Abdan Bayan; Siregar, Purnama Dewi; Buhori, Raja Muhammad Rafian; Sulastri (BKM Public Health and Community Medicine, 2024)
Purpose: Establishing a bullying prevention and case management system for adolescents in Junior High School. Content: The establishment of this system is based on law No.35 of 2014 the policies interpreted as efforts to prevent and handle violence against children and creating a safe and comfortable learning environment. Implementation of this law is still not optimal due to the lack of involvement from all parties included. Schools are expected to collaborate in creating policies in the form of a decree to initiate a bullying prevention and intervention system in schools, supported by conducting socialization and seminars regarding the roles of teachers, parents, and students in addressing bullying cases. Additionally, the formation of peer counselors in schools through collaboration between the school and health centers or universities is encouraged.It is expected that the number of bullying cases can be reduced and prevented, the availability of reporting services for students that makes students feel safe and comfortable at school, and school will get resources from collaborations with many parties. Challenges in implementing this system include limited resources, both financially and human resources available, inconsistencies in efforts to build the system due to the long time frame, mismatch of visions and missions, and lack of coordination among all parties involved. The strengths of this system are the support from students and parents to protect their right, improved student achievement, an efficient mechanism for handling bullying cases, and creating an inclusive school culture. Implementation of this system can address bullying cases and create an optimal learning environment in schools.